(Self)Censored at Home and Away: Richard Wright’s Native Son (1940) in Spanish - Daniel Linder (Mutatis Mutandis, 2023)
Native Son (Harper & Brothers, 1940), by Richard Wright (1908, Roxie, Mississippi–1960, Paris, France), contained a scene rewritten by the author to satisfy the Book of the Month Club, which had selected a Black author for the first time. In the censored scene, the main character, Bigger Thomas, engages in a lewd sexual act; other potentially offensive contents, however, were not subjected to the same treatment. The first Spanish translation, Sangre negra (Sudamericana, 1941), was banned in Spain twice (1944 and 1953) when the Argentinian publishers attempted to import it into the strongly autocratic country ruled by Francisco Franco from 1939 to 1975. The translation, by Pedro Lecuona, was finally published in Spain in 1987, under the literal title Hijo nativo (Ediciones Versal and Círculo de Lectores), with a revised text for the European-Spanish readership. The state censorship that banned this translation from Spain, the self-censorship that the Argentinian translation contains, and the Iberian revisions are all examined closely. In 1991, the Library of America published an uncensored edition which restored the unexpurgated text. However, Lecuona’s (revised) translation circulated until 2022, when an unexpurgated text, Hijo de esta tierra (Alianza Editorial) by Eduardo Hojman, was made from the restored text of this hugely significant example of African-American literature. This edition restores all previously (self)censored segments and also contains the first Spanish version of the epilogue “How Bigger Was Born”. Book reviews and social media reception pinpoint the importance of Wright’s contribution but are neglectful of this retranslation’s fascinating history